Solar Drying for Domestic and Industrial Applications: A Comprehensive Review of Innovations and Efficiency Enhancements - Md Atiqur Rahman; S. M. Mozammil Hasnain; Prabhu Paramasivam; Rustem Zairov; Abinet Gosaye Ayanie (Global Challenges)
Abstract Global challenges such as energy scarcity and food security are intensified by a growing population and substantial post‐harvest food losses, contributing to alarming hunger levels. Solar drying is recognized as an effective, high‐quality, and sustainable method for food preservation, significantly aiding global food security. Dryers are essential in agriculture and the food industry for extending crop shelf life by removing moisture through thermal energy, with solar thermal energy being particularly suitable due to its environmental benefits and availability. This article reviews the classification of solar dryers, including direct (DSD), indirect (ISD), and hybrid (HSD) systems, examining key components like solar collectors, drying chambers, and auxiliary systems and the factors affecting their performance. The review highlights that the efficiency of solar dryers depends on dryer type, solar irradiation, drying duration, and operational conditions. Recent advancements to enhance solar dryers' energy efficiency include hybrid systems incorporating auxiliary heating sources (electric or biomass), solar‐assisted heat pump dryers, surface modification techniques, and heat storage systems utilizing sensible and latent heat storage. Findings suggest that HSD with auxiliary units can achieve up to 54% efficiencies, while solar collectors can reach up to 81%, yielding better product quality than traditional ones.